III. Ventricle diameter increase during ventricular drainage challenge – A predictor of shunt dependency after subarachnoid hemorrhage. (February 2020) - Weigl, Carolin; Bruendl, Elisabeth; Schoedel, Petra; Schebesch, Karl-Michael; Brawanski, Alexander; Kieninger, Martin; Bele, Sylvia
Highlights: We found a simple way for determining shunt dependency following aneurysmal subarachnoid hemorrhage by measuring the width of the third ventricle during ventricular drainage challenge. Abstract: Hydrocephalus with the need for shunt placement is a common sequela after aneurysmal subarachnoid hemorrhage (aSAH). In 2009 Chan et al. published a formula to predict shunt dependency in SAH patients, the failure risk index (FRI). We reevaluated the FRI within the aSAH population in our hospital and wanted to identify easier measurements forecast shunt dependency. We retrospectively analyzed data from patients with aSAH treated in our neuro-intensive care unit and calculated the FRI according to the paper by Chan et al. 2013 and data were compared to the results of Chan et al . 38 patients were included in this study, 24 female and 14 male. 38% suffered a SAH WFNS I, 19% WFNS II, 24% WFNS III, 5% WFNS IV and 14% WFNS V. 17 patients underwent a shunt implantation (group 1), 21 patients did not (group 2). The calculated FRI Index did not correlate with the expectancy of shunt implantation in 22% of the cases (group 1). In group 2 the FRI index and the prediction of shunt dependency did not match in 33% of the cases. Furthermore, we found the increase of the third ventricle diameter to be predictive in 67% for failed EVD challenge and the decrease of the third ventricle diameter predictive in 67% for successful EVD challenge. In this study, we were not able to confirm the results of the FRI designed by Chan et al within our patient population. Furthermore, we consider the increase of the third ventricle diameter to be a simpler and more reliable predictor of shunt dependency.